Silybum marianum (L.) Gaertn’den Silymarin Ekstraksiyon Koşullarının Optimizasyonu ve Miktar Tayini için HPLC Yönteminin Geliştirilmesi - AKBEL, Erten; KARA, Mustafa (ISPEC Tarım Bilimleri Dergisi, 2024)
Silybum marianum (milk thistle) and its derivatives are used in the treatment of many diseases, especially liver diseases. In this study, extraction variables required for the industrial process of Silybum marianum (L.) Gaertner, and conditions for silymarin extraction were optimized using RSM (Response surface methodology). For this purpose, the fixed oil content was determined to be approximately 27% in the extraction using hexane in a Soxhlet apparatus with fruits of certain particle size. An HPLC technique was devised and approved to determine the amount of silymarin in the extract. The HPLC method’s linearity was assessed using solutions containing 5 to 30 µg/ml silymarin. A selective, rapid, accurate, precise chromatographic method was was devised and approved to determine the amount of silymarin in plants. Using an Agilent Extend C18 column (250 x 4.6 mm, 5 µm) column, chromatographic separation was carried out. Ultrapure water containing 0.1% formic acid and acetonitrile (67/33, v/v) were used as mobile phase at a flow rate of 1.0 ml min-1. Eluents were detected at 288 nm using a UV detector. The results showed that the liquid chromatographic method was linear, precise, accurate, robust, with RSD values below 1.00% and recovery percentage within the standard limits (99-101%). The extracted silymarin yield was calculated to be 0.237% under finest settings.